(Liquid + liquid) phase equilibrium and critical behavior of binary solution {heavy water + 2, 6-dimethylpyridine}. (September 2015) - Xu, Chen; Chai, Shouning; Yin, Tianxiang; Chen, Zhiyun; Shen, Weiguo
Highlights: Coexistence curves, heat capacities and turbidities were measured. Deuterium effect on coexistence curves was discussed. Universal critical amplitude ratios were tested. Asymmetry of coexistence curves was analyzed by the complete scaling theory. Abstract: The (liquid + liquid) coexistence curves, the isobaric heat capacities per unit volume and the turbidities for the binary solution of {heavy water + 2, 6-dimethylpyridine} have been precisely measured. The values of the critical exponents were obtained, which confirmed the 3D-Ising universality. It was found that the critical temperature dropped by 5.9 K and the critical amplitude of the coexistence curve significantly increased as compared to the binary solution of {water + 2, 6-dimethylpyridine}. The complete scaling theory was applied to well describe the asymmetric behavior of the diameter of the coexistence curve as the heat capacity contribution was considered. Moreover, the values of the critical amplitudes of the correlation length and the osmotic compressibility were deduced, which together with the critical amplitudes of the coexistence curve and the heat capacity to test universal amplitude ratios.